Determination of Atropine Sulfate in Human Urines by Capillary Electrophoresis Using Chemical Modified Electrode as Electrochemiluminescence Sensor - Min Zhou; Juan Mi; Yujie Li; Huashan Zhang; Yanjun Fang (International Journal of Electrochemistry)
A Ru(bpy)3 2+-based electrochemiluminescence (ECL) detection coupled with capillary electrophoresis (CE) was developed for the determination of atropine sulfate on the basis of an Eu-PB modified platinum electrode as the working electrode. The analyte was injected to separation capillary of 50 cm length (25 μm i.d., 360 μm o.d.) by electrokinetic injection for 10 s at 10 kV. Parameters related to the separation and detection were discussed and optimized. It was proved that 10 mM phosphate buffer at pH 8.0 could achieve the most favorable resolution, and the high sensitivity of detection was obtained by using the detection potential at 1.15 V and 5 mM Ru(bpy)3 2+ in 80 mM phosphate buffer at pH 8.0 in the detection reservoir. Under the optimized conditions, the ECL peak area was in proportion to atropine sulfate concentration in the range from 0.08 to 20 μg⋅mL−1 with a detection limit of 50 ng⋅mL−1 (3σ). The relative standard derivations of migration time and peak area were 0.81 and 3.19%, respectively. The developed method was successfully applied to determine the levels of atropine sulfate in urine samples of patients with recoveries between 90.9 and 98.6%.